The Study of the Cross-Sectional Areas of the Gluteal Muscles on Magnetic Resonance Images of the Weighlifting Athletes - erdağı, kenan; Işık, Bülent (Progress in Nutrition, 2021)
Gluteus maximus is the most important extensor and lateral rotator of the hip. It is often used to accelerate the body upward and forward from a position of hip flexion. Mm. glutei medius and minimus are referred to as small gluteal muscles. Both muscles are the most important abductors and medial rotators of the thigh. Their action stabilises the hip during standing and walking and prevents the tilting of the pelvis to the contralateral side while standing on one leg. This study aims to examine the cross-sectional areas of the gluteus maximus, gluteus medius and gluteus minimus muscles on magnetic resonance images of olympic style weightlifting athletes (male n= 15, female= 12) and sedentary individuals (male n= 15, female= 12). This study included asymptomatic athletes in olympic style weightlifting (male n= 15, age: 20.00±2.54; female n= 12, age: 20.75±1.49) and sedentary individuals (male n= 15, age: 19.93±2.15; female; n= 12, age: 20.75±1.36). The cross-sectional areas of the gluteus maximus, gluteus medius and gluteus minimus muscles were assessed bilaterally using magnetic resonance imaging. It was observed that the cross-sectional areas of the right and left gluteus maximus of male weightlifting athletes were larger than those of sedentary males (z(28)= 2.013, p< .05, z(28)= 1.991, p < .05; respectively). Similarly, it was also found that that the cross-sectional areas of the right and left gluteus maximus of female weightlifting athletes were larger than those of sedentary females (z(22)= 3.296, p< .001, z(22)= 3.726, p < .001; respectively). No significant difference was observed for the cross-sectional areas of the gluteus medius and gluteus minimus muscles between the athlete and sedentary groups (p>.05). It might be stated that olympic style weightlifting trainings have a hypertrophic effect on the cross-sectional area of the gluteus maximus muscle of the athletes.